Development of a novel alcohol and nicotine concurrent access (ANCA) self-administration procedure in baboons. (1st January 2020) - Holtyn, August F.; Davis, Catherine M.; Weerts, Elise M.
Highlights: Co-self-administration of alcohol and nicotine was established in baboons. Alcohol and nicotine intake was similar during single and concurrent access. Varenicline reduced co-self-administration of both alcohol and nicotine. Abstract: Background: Self-administration of either alcohol or nicotine under single-access conditions has been studied extensively in laboratory animals. Relatively few studies have examined the co-use of these substances, even though alcohol and nicotine use and abuse commonly co-occur in humans. The objectives of this study were to develop a baboon model of concurrent alcohol and nicotine self-administration, and examine effects of varenicline on alcohol and nicotine co-use. Methods: In Experiment 1, five male baboons were trained to self-administer drinks of alcohol (4% w/v) and injections of nicotine (0.032–0.1 mg/kg) under single-access and then concurrent-access conditions, and intake of alcohol (g/kg) and nicotine (mg/kg) was compared under single- and concurrent-access conditions. In Experiment 2, three male baboons self-administered drinks of alcohol (4% w/v) and injections of nicotine (0.056 mg/kg) under concurrent-access conditions. Pretreatment with varenicline (0.32–1.0 mg/kg, s.c.) or an equal volume of its vehicle before concurrent-access sessions was repeated for 5 consecutive days. Results: Self-administration of nicotine and alcohol was successfully established under both single- and concurrent-access conditions that produced reliable levels of voluntary alcohol and nicotine intake. Co-self-administration of both drugs produced levels of intake similar to that produced by each drug alone. Varenicline significantly reduced intake of both alcohol and nicotine when compared to the vehicle condition. Conclusions: This baboon model provides a valuable tool for further investigation of the behavioral and pharmacological mechanisms involved in co-use of nicotine and alcohol. A single pharmacotherapeutic agent (e.g., varenicline) may be useful in treating nicotine and alcohol co-use.